The Spanish crime novel. A contemporary example: Dolores Redondo (XXI Century. Spanish Literature and Culture, 2016)
This article states that the crime novel is successful and enjoys great prestige in the current Spanish literary scene. After a brief historical tour through the origins of this genre and the several reasons that explain its growth, the main aim of the text is to highlight Dolores Redondo as an important author in the history of the Spanish crime novel by reading her books and consulting the different interviews that provide us her kindest point of view.
Keywords: Dolores Redondo; detective novel; society; woman; crime